2018
DOI: 10.1097/dcr.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Total Mesorectal Excision vs Laparoscopic Total Mesorectal Excision in the Treatment of Low and Middle Rectal Cancer: A Propensity Score Matching Analysis

Abstract: Transanal total mesorectal excision is a safe and feasible technique that results in a high-quality rectal cancer resection specimen and favorable 30-day postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 26 publications
4
46
0
1
Order By: Relevance
“…In the present study, patients who underwent TaTME were more often diverted during primary surgery. A recent single-centre case-matched study found similar results [25]. This difference might reflect surgeons' perception to protect the anastomosis following the new approach whilst this risk is unsubstantiated.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, patients who underwent TaTME were more often diverted during primary surgery. A recent single-centre case-matched study found similar results [25]. This difference might reflect surgeons' perception to protect the anastomosis following the new approach whilst this risk is unsubstantiated.…”
Section: Discussionmentioning
confidence: 81%
“…6 Since 2015, this combined transabdominal transanal approach is registered on the mandatory Dutch Colorectal Audit (DCRA). The first published international cohort studies 7,8 and small matched comparative studies [9][10][11][12][13][14] reported promising results for TaTME in rectal cancer, including decreased involved resection margins, lower conversion rates, and morbidity comparable to that with lapTME. It has also been shown that TaTME has a substantial learning curve.…”
mentioning
confidence: 99%
“…One thousand two hundred and forty-seven citations were retrieved from the search strategy. Finally, twelve studies [24][25][26][27][28][29][30][31][32][33][34][35] were included in the analysis, with a total of 899 patients (411 patients in TaTME group, 488 patients in LaTME group) ( Figure 1). The characteristics of eligible studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…There were six studies [24-27, 31, 34] that reported CRM, eleven studies [24][25][26][28][29][30][31][32][33][34][35] that reported positive CRM, eight studies [24-27, 30, 32-34] that reported DRM and five studies [25,28,31,34,35] that reported positive DRM. No differences were found in these pathological outcomes ( Figure 5).…”
mentioning
confidence: 99%